2007
DOI: 10.1007/s10453-007-9058-y
|View full text |Cite
|
Sign up to set email alerts
|

Status of airborne spores and pollen in a coir factory in Kerala, India

Abstract: The prevalence of airborne fungal spores and pollen grains in the indoor and outdoor environ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As In addition, the concentration observed during January month is 5 times more than that of March month. The present study revealed that the highest fungal concentrations at all the sites were observed in January and February month which is in close proximity with the results of the previous study conducted in a coir, sawmill, chlor-alkali and our mill, that had obtained the maximum spore count in winter months due to low rainfall, moderate temperature, and relatively high humidity, favouring fungal sporulation (Nayar et al, 2007;Jothish & Nayar, 2004;Nayak et al, 1998;Misra and Jamil, 1991). In this study, the meteorological parameters, suitable growth substrate, and crushed sugarcane, especially at the cutter site might have provided the growth of fungi.…”
Section: Variation Of Fungal Bioaerosol During the Study Periodsupporting
confidence: 90%
See 1 more Smart Citation
“…As In addition, the concentration observed during January month is 5 times more than that of March month. The present study revealed that the highest fungal concentrations at all the sites were observed in January and February month which is in close proximity with the results of the previous study conducted in a coir, sawmill, chlor-alkali and our mill, that had obtained the maximum spore count in winter months due to low rainfall, moderate temperature, and relatively high humidity, favouring fungal sporulation (Nayar et al, 2007;Jothish & Nayar, 2004;Nayak et al, 1998;Misra and Jamil, 1991). In this study, the meteorological parameters, suitable growth substrate, and crushed sugarcane, especially at the cutter site might have provided the growth of fungi.…”
Section: Variation Of Fungal Bioaerosol During the Study Periodsupporting
confidence: 90%
“…The rural population directly or indirectly involved in the sugar industries are exposed to signi cant amount of pollution generated within and around the mills. Besides, many studies have been conducted on fungal bioaerosol emission from land ll sites (Srivastava et al, 2021), academic institution (Gupta et al, 2021), waste paper and cardboard recycling industries (Baghani et al, 2021), Museum (Awad et al, 2019), sewage treatment plants (Maharia et al, 2015), coir factory (Nayar et al, 2007), sawmill (Jothish and Nayar, 2004), whereas no such studies have been carried out on sugar mill. By considering the lacunae of the bioaerosol data from the sugar mill, the study was designed to assess the fungal bioaerosol concentration in different sites, determining the effects of meteorological factors and assessment of health hazards associated with the exposed workers within the mill.…”
Section: Introductionmentioning
confidence: 99%
“…A number of data are: 0:163, 1: 69, 2:46, 3:31, 4:25, 5:20, 6:18, 7:13, 8:12, and 9:10 in the present case could be Leptosphaeria type 1, although this was one of the most frequent ascospore types found. Indeed, this difficulty in identifying ascospores is reflected in the small number of types identified in the literature: for instance, only one type (Dames and Cadman 1994;Lim et al 1998;Jothish and Nayar 2004;Ho et al 2005;Gillum and Levetin 2008), 2 types (Li and Kendrick 1995a, b;Nayar et al 2007 The annual mean concentration of ascospores found in the present study is comparable with other values reported in the literature: Halwagy (1994) with about 130 ascospores/m 3 in Kuwait; Dames and Cadman (1994) with 177 ascospores/m 3 in Durban, South Africa; De Antoni-Zoppas et al (2006) with 136 ascospores/m 3 in Caixas do Sul, Brazil; and Gillum and Levetin (2008) with 194 and 250 ascospores/m 3 in two places in Oklahoma, USA. Autumn and winter were the seasons when ascospores were most frequent, although the actual month with the greatest concentration varied, being September in 1 year and December and October in the other.…”
Section: Discussionmentioning
confidence: 98%
“…Although most of them produce conidiospores or conidia for asexual reproduction, they are recognized by the formation of meiospores named ascospores (Blackwell and Spatafora 2004). Monitoring of airborne spores has found these ascospores to be present in the outdoor air in very diverse proportions that range 0.59-28.6% (Shaheen 1992;Halwagy 1994;Dames and Cadman 1994;Li and Kendrick 1995b;Lim et al 1998;Chakraborty et al 2003;Adhikari et al 2004;Jothish and Nayar 2004;Ho et al 2005;Oliveira et al 2005;Díez-Herrero et al 2006;De Antoni-Zoppas et al 2006;Nayar et al 2007;Nunes et al 2008;Gillum and Levetin 2008;Das and Gupta-Bhattacharya 2008).…”
Section: Introductionmentioning
confidence: 96%